Relation of arterial stiffness to diastolic dysfunction in hypertensive heart disease. Issue 12 (14th November 2005) - Mottram, P M; Haluska, B A; Leano, R; Carlier, S; Case, C; Marwick, T H
Abstract : Objectives: To examine the relation of arterial compliance to diastolic dysfunction in hypertensive patients with suspected diastolic heart failure (HF). Patients: 70 medically treated hypertensive patients with exertional dyspnoea (40 women, mean (SD) age 58 (8) years) and 15 normotensive controls. Main outcome measures: Mitral annular early diastolic velocity with tissue Doppler imaging and flow propagation velocity were used as linear measures of diastolic function. Arterial compliance was determined by the pulse pressure method. Results: According to conventional Doppler echocardiography of transmitral and pulmonary venous flow, diastolic function was classified as normal in 33 patients and abnormal in 37 patients. Of those with diastolic dysfunction, 28 had mild (impaired relaxation) and nine had advanced (pseudonormal filling) dysfunction. Arterial compliance was highest in controls (mean (SD) 1.32 (0.58) ml/mm Hg) and became progressively lower in patients with hypertension and normal function (1.04 (0.37) ml/mm Hg), impaired relaxation (0.89 (0.42) ml/mm Hg), and pseudonormal filling (0.80 (0.45) ml/mm Hg, p  =  0.011). In patients with diastolic dysfunction, arterial compliance was inversely related to age (p  =  0.02), blood pressure (p < 0.001), and estimated filling pressures (p < 0.01) and directly related to diastolic function (p < 0.01). After adjustment for age, sex, body size, blood pressure, and ventricular hypertrophy, arterial compliance was independently predictive of diastolic dysfunction. Conclusions: In hypertensive patients with exertional dyspnoea, progressively abnormal diastolic function is associated with reduced arterial compliance. Arterial compliance is an independent predictor of diastolic dysfunction in patients with hypertensive heart disease and should be considered a potential target for intervention in diastolic HF.